Comparison of Eco - Scale Between UV - Vis Spectrophotometry and Thin Layer Chromatography - Densitometry Methods on The Determinination of Retinoic Acid in Facial Cream Preparations - Zaneta Nur Faida; Mohammad Alauhdin (Journal of Science and Technology Research for Pharmacy, 2024)
Retinoic acid, a compound derived from vitamin A and its active metabolites, is often found in cream preparations and can be used without a doctor's prescription. This research aims to analyze the retinoic acid content in facial cream preparations and determine the environmental friendliness of the analytical method used. The materials used in this research were PBFI retinoic acid, methanol, TLC plates, n-hexane, acetone, and three facial cream samples. UV - Vis Spectrophotometry and Thin Layer Chromatography - Densitometry are methods used for assay analysis and Eco - Scale is a method for determining greenness. The research found that three cream samples tested positive for retinoic acid, which has been banned by BPOM since 1999. The UV-Vis Spectrophotometry method measured retinoic acid content of 0.103%, 0.266% and 0.256%, with a total score of 24 points. The Thin Layer Chromatography - Densitometry method measured retinoic acid content of 0.0213%, 0.0314%, and 0.027%, with a score of 50 points. It can be concluded that the UV - Vis Spectrophotometry method is more environmentally friendly compared to the Thin Layer Chromatography - Densitometry method based on Eco - Scale analysis.